Responding to Pluralism: The Relevance of Christological and Soteriological Distinctiveness within the Framework of Contemporary Reformed Apologetics - Riki Ardianto; Daniel Octavianus; Didit Yuliantono Adi (STT Transformasi Indonesia Manado, 2026)
This paper is motivated by the dynamics of religious pluralism that challenge the traditional understanding of Christ's uniqueness as Savior of the world, especially amidst the growing relativism of truth and interfaith dialogue. In this context, in-depth and argumentative theological reflection is essential for the Christian faith to remain relevant and accountable. This study aims to comprehensively examine the uniqueness of Jesus Christ from the perspective of Christology and Soteriology, and to examine how an apologetic approach can be used to explain and defend this doctrine rationally and contextually. The research method used is qualitative with a literature study approach and descriptive-analytical analysis, through the study of various theological sources, both the Bible and classical and contemporary academic literature. The results show that Christ's uniqueness lies in His identity as God incarnate as a human being and His final and universal work of salvation for humanity. From an apologetic perspective, this uniqueness can be explained through historical arguments regarding Christ's life and resurrection, as well as philosophical-theological reflections that affirm the consistency of the Christian doctrine of salvation. Furthermore, this approach allows for open dialogue without losing the integrity of faith. The research conclusion confirms that the uniqueness of Christ as the Savior of the world is the center of Christian faith which has a strong theological and rational basis, and remains relevant to be communicated contextually in a pluralistic society.